2018
DOI: 10.1155/2018/1362958
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surface Nanotopography and Calcium Chemistry of Titanium Bone Implants on Early Blood Platelet and Macrophage Cell Function

Abstract: Early responses of blood platelets and immunoinflammatory cells (macrophages) to titanium (Ti) bone implants affect the subsequent biological healing of implants by modulating early tissue healing-microenvironments via the formation of temporary fibrin matrix scaffolds for stem cell migration and production of growth factors and cytokines. This study investigated the effects of nanoscale surface topography and calcium ion (Ca2+) modification of Ti surfaces on biocompatibility regulated by blood platelets and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 32 publications
(61 reference statements)
0
23
0
Order By: Relevance
“…The post-anodization treatment with H 2 O 2 and subsequent Col-I binding with the EPF method rendered the surface hydrophilic. A study published by Park et al 36 showed that nano-topography positively modulated the immediate blood platelet function and early macrophage immunoinflammatory response. Our results indicated that the nano-topography has a marked effect on the release of TGF-β and a slight stimulatory effect on PDGF-AB, which was masked by the greater influence of Col-I coatings.…”
Section: S S S S S S S S St T T T T T T T T N N N N N N N N Nt T T Tmentioning
confidence: 99%
“…The post-anodization treatment with H 2 O 2 and subsequent Col-I binding with the EPF method rendered the surface hydrophilic. A study published by Park et al 36 showed that nano-topography positively modulated the immediate blood platelet function and early macrophage immunoinflammatory response. Our results indicated that the nano-topography has a marked effect on the release of TGF-β and a slight stimulatory effect on PDGF-AB, which was masked by the greater influence of Col-I coatings.…”
Section: S S S S S S S S St T T T T T T T T N N N N N N N N Nt T T Tmentioning
confidence: 99%
“…To date, many studies have addressed the key roles of Ti implants in anti-inflammatory responses and have emphasized the important role of nanostructured surfaces. 44,[51][52][53][54] However, most of these studies have focused on the proliferation, adhesion, and secretion of pro-inflammatory cytokines from macrophages on the material. [53][54][55] Yao et al similarly used different voltages to fabricate nanotube surfaces and found that larger nanotubular surfaces (120 nm) could inhibit the expression and secretion of pro-inflammatory cytokines in macrophages.…”
mentioning
confidence: 99%
“…A second approach is through application of in situ forming drug carriers, where they undergo a sol-gel transition from a low viscous liquid and into a gel (Figure 1.3) (Hossen et al 2019). Third option for regional therapies is the implantation of solid materials that have surface-altered calcium or titanium modifications, carried out in treatment for bone cancer at present (Park et al 2018).…”
Section: Sustained and Local Delivery As An Approach To Therapymentioning
confidence: 99%
“…Use of both natural and synthetic polymers for local drug delivery has been observed in cancer therapeutics. Natural polymers have been based on polysaccharides, such as chitosan, alginate dextran etc, or polypeptides using gelatine, albumin, collagen, or silk (Kim et al 2015;Newland et al 2018;Park et al 2018). Synthetic polymers are usually preferred to natural-based ones due to the ability to easily modify specific properties like degradation, biocompatibility, mechanical properties, and drug release etc.…”
Section: Sustained and Local Delivery As An Approach To Therapymentioning
confidence: 99%
See 1 more Smart Citation